2019
DOI: 10.1002/stem.3061
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical translation of exosomes derived from mesenchymal stem/stromal cells

Abstract: Exosomes are nanovesicles secreted by virtually all cells. Exosomes mediate the horizontal transfer of various macromolecules previously believed to be cell-autonomous in nature, including nonsecretory proteins, various classes of RNA, metabolites, and lipid membrane-associated factors. Exosomes derived from mesenchymal stem/stromal cells (MSCs) appear to be particularly beneficial for enhancing recovery in various models of disease. To date, there have been more than 200 preclinical studies of exosome-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
162
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 59 publications
0
162
1
1
Order By: Relevance
“…Extracellular vesicles are actively released by living cells by mechanisms which can be experimentally manipulated 20,21 and contain surface proteins that can confer tropism for specific cell types or tissues 22 . Moreover, nucleic acid loaded 23 or unmodified 24 EVs have shown therapeutic potential and are moving toward clinical use. On the contrary, the origin of extracellular ribonucleoproteins is controversial 25 and it is still unclear whether they are released actively from cells 26 or they constitute stable intracellular complexes passively released by distressed, damaged or dying cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles are actively released by living cells by mechanisms which can be experimentally manipulated 20,21 and contain surface proteins that can confer tropism for specific cell types or tissues 22 . Moreover, nucleic acid loaded 23 or unmodified 24 EVs have shown therapeutic potential and are moving toward clinical use. On the contrary, the origin of extracellular ribonucleoproteins is controversial 25 and it is still unclear whether they are released actively from cells 26 or they constitute stable intracellular complexes passively released by distressed, damaged or dying cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent concise review found that there are over 200 preclinical studies of EV‐based therapies in a number of different animal models . For example, a recent paper showed that EVs derived from human AF‐derived stem cells could enhance cardiac function in mice .…”
Section: Preclinical Studies and Clinical Trials In Fetal Therapymentioning
confidence: 99%
“…A recent concise review found that there are over 200 preclinical studies of EV-based therapies in a number of different animal models. 72 For example, a recent paper showed that EVs derived from human AF-derived stem cells could enhance cardiac function in mice. 73 Also, MSC derived from the human UC have been shown to reduce neuroinflammation and induce neuroregeneration in perinatal brain injury in 3-day old Wistar rat brains.…”
Section: Alpha-thalassemia Majormentioning
confidence: 99%
“…The secretion of cytokines with anti-inflammatory properties such as transforming growth factor beta (TGFb) and interleukin (IL)-10 can lead to the suppression of immune cells involved in antitumor immunity, such as CD8+ T cytotoxic cells and DCs [27][28][29][30][31][32][33][34][35]. These cytokines can also induce immune cells with immunosuppressive properties such as regulatory T lymphocytes (Tregs) and myeloid derived suppressor cells (MDSCs), which permit tumors to evade immunosurveillance and elimination [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%